Meningkatkan Kesadaran Masyarakat Tentang Bahaya Narkoba Melalui Program Pengabdian - Endam Apulina Br Sembiring (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Drug abuse is a health and social problem that has a broad impact on individuals, families, and communities. Low public knowledge and awareness of the dangers of drugs is one factor contributing to the increase in drug abuse cases. This Community Service program aims to increase public knowledge and awareness of the dangers of drugs through education and outreach activities. Implementation methods include health education, interactive discussions, educational media screenings, and evaluation through pre- and post-tests. The results of the program indicate an increase in public knowledge and attitudes regarding the dangers of drugs, as well as a commitment to avoiding drug abuse. This program is expected to contribute to efforts to prevent drug abuse in the community.